Refractive Error and Ocular Biometric Changes in the Treatment of Diabetes Mellitus - Amir Asharlous; Abbas Riazi; Samira Janani; Sattar Rajabi; Amir Rakhshan; Mehdi Khabazkhoob; Zahra Sadat Dibaji Forooshani; Hamed Tabesh (Function and Disability Journal, 2023)
Background and Objectives: Evaluation of changes in refractive errors and biometric parameters in the process of glycemic control in people with type 2 diabetes during three-month treatment. Methods: Patients with the first diagnosis of type 2 diabetes or a history of poor glycemic control (hemoglobin glycate more than 7.5%) and without any systemic disease other than diabetes were included. Hemoglobin glycate, refractive error, and biometric parameters were evaluated before treatment and one and a half and three months after treatment, and their changes were examined by generalized estimating equation (GEE) analysis. Results: A total of 60 eyes of 30 patients with a mean age of 51.63±6.79 years were evaluated. Hemoglobin glycate decreased by an average of 1.028% compared to the baseline measurement in the third month (P<0.001). Mean spherical (P=0.554), spherical equivalent (P=0.340), axial length (P=0.147), and anterior chamber depth (P=0.336) did not show a significant difference between the three examinations. In contrast, the lens thickness showed a significant decrease during treatment (P=0.001). Finally, generalized estimating equation (GEE) analysis showed that a 1% decrease in hemoglobin glycate increased by 0.226 mm. (P=0.002) in the axial length. It should be mentioned in tables FU1means Follow-up 1.5 months and FU2 means Follow-up 3 months. Conclusion: The present study shows that refractive errors and most ocular biometric parameters do not change significantly compared to the baseline levels in the period of one and a half and three months after the start of glycemic control.